Reconsidering the technologies of intellectual inquiry in curriculum design. Issue 4 (2nd October 2017) - Costa, Cristina; Harris, Lisa
ABSTRACT: This paper reports on the design and delivery of classroom pedagogies and students' engagement with it in two different UK universities. Under the banner of curriculum design and Bourdieu's curriculum principles, the study set out to create modules that provided students with an interdisciplinary perspective on how the web is changing the way citizens live, interact and learn. Focusing on the idea that the web is becoming a tool of intellectual inquiry and an instrument of reproduction of knowledge inequality, the goal of this research was to transform knowledge practices by encouraging a learning habitus that relies on knowing how to learn rather than becoming 'knowledgeable.' The paper concludes that the Bourdieuian perspective on curriculum design still holds currency in the digital age, given that it shares an epistemology of practice similar to that advocated by a digital participatory culture. We also offer a critique to our approach, using Bourdieu's logic of practice to examine how education as a field displays (hidden) rules that students embody as their learning habitus. As students' learning practices become doxified through their educational trajectories, learners find it difficult to engage with a curriculum that aims to diversify pedagogical structures and reflect a changing society.